Pemetaan Aset Komunal Pariwisata Untuk Mendukung Kampung Wisata Menjadi Kampung Budaya Berkelanjutan Di Bamboo Mewek Park Kota Malang - Mareta Syifa Primadianty; Melati Julia Rahma; Yudi Winarno (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Community-based tourism village management still faces challenges in utilizing local potential to build cultural identity, preserve the environment, and improve community welfare. This study aims to map communal tourism assets in Bamboo Mewek Park (BMP), Malang City, as a strategy to strengthen community-based tourism toward a sustainable cultural village. The Asset-Based Community Development (ABCD) method was applied to identify seven key assets: physical, financial, environmental, technological, human, social, and spiritual. Data were obtained through interviews, observations, and documentation, then analyzed qualitatively using source triangulation. The findings reveal that the interconnection among assets forms a participatory tourism system that reinforces the community’s social, economic, and cultural resilience. Traditional arts serve as core social and cultural assets that drive financial and environmental sustainability, while spiritual and social solidarity values serve as moral foundations for community-based management. The novelty of this research lies in applying the ABCD approach within an urban tourism village context, showing how collaboration among communities, academics, and government institutions transforms local assets into sustainable socio-cultural capital.